Comparative Transcriptomic Analysis of Virulence Factors in Leptosphaeria maculans during Compatible and Incompatible Interactions with Canola - Sonah, Humira; Zhang, Xuehua; Deshmukh, Rupesh K.; Borhan, M. Hossein; Fernando, W. G. Dilantha; Bélanger, Richard R. (Frontiers in Plant Science, 2016)
Leptosphaeria maculans is a hemibiotrophic fungus that causes blackleg of canola (Brassica napus), one of the most devastating diseases of this crop. In the present study, transcriptome profiling of L. maculans was performed in an effort to understand and define the pathogenicity genes that govern both the biotrophic and the necrotrophic phase of the fungus, as well as those that separate a compatible from an incompatible interaction. For this purpose, comparative RNA-seq analyses were performed on L. maculans isolate D5 at four different time points following inoculation on susceptible cultivar Topas-wild or resistant near isogenic line Topas-Rlm2. Analysis of 1.6 billion Illumina reads readily identified differentially expressed genes that were over represented by candidate secretory effector proteins, CAZymes, and other pathogenicity genes. Comparisons between the compatible and incompatible interactions led to the identification of 28 effector proteins whose chronology and level of expression suggested a role in the establishment and maintenance of biotrophy with the plant. These included all known Avr genes of isolate D5 along with eight newly characterized effectors. In addition, another 15 effector proteins were found to be exclusively expressed during the necrotrophic phase of the fungus, which supports the concept that L. maculans has a separate and distinct arsenal contributing to each phase. As for CAZymes, they were often highly expressed at 3 dpi but with no difference in expression between the compatible and incompatible interactions, indicating that other factors were necessary to determine the outcome of the interaction. However, their significantly higher expression at 11 dpi in the compatible interaction confirmed that they contributed to the necrotrophic phase of the fungus. A notable exception was LysM genes whose high expression was singularly observed on the susceptible host at 7 dpi. In the case of TFs, their higher expression at 7 and 11 dpi on susceptible Topas support an important role in regulating the genes involved in the different pathogenic phases of L. maculans. In conclusion, comparison of the transcriptome of L. maculans during compatible and incompatible interactions has led to the identification of key pathogenicity genes that regulate not only the fate of the interaction